2018
DOI: 10.13189/ujer.2018.060516
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Science Teaching Enriched with Technological Practices on Attitudes of Secondary School 7<sup>th</sup> Grade Students towards Science Course

Abstract: Purpose of this research is to examine effect of science teaching enriched with technological practices on attitude levels of secondary school 7 th grade students towards science course. Execution step of the research was performed on 7 th grade students attending to a government secondary school in Turkey in the academic year of 2015 and completed in 13 weeks. Workgroup of the study had 74 students (control group = 38, experiment group = 36). "The Attitude towards Science Course Scale" was used to collect dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Thus, hypothesis three which states that boys' and girls' performances in EG vary is rejected. The findings concur with the studies by Okwuduba et al (2018) and Mihindo et al (2017), who investigated the impact of computer simulations on gender and found no significant differences among male and female secondary school learners' performance in stoichiometry. They attributed the improvement to computers used in the activities.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Thus, hypothesis three which states that boys' and girls' performances in EG vary is rejected. The findings concur with the studies by Okwuduba et al (2018) and Mihindo et al (2017), who investigated the impact of computer simulations on gender and found no significant differences among male and female secondary school learners' performance in stoichiometry. They attributed the improvement to computers used in the activities.…”
Section: Discussionsupporting
confidence: 91%
“…Conversely, learners from EG found CS very interesting. These observations agree with Yildirim and Sensoy (2018), who indicated dynamic interactive visual representations are necessary to enhance academic performances and learners' interests. They further alluded that attitude is one of the critical factors determining learners' performance in science.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The era of technology has come to stay and teaching is expected to be facilitated by the use of technology. This is supported by Yildirim and Sensoy (2018) that educational system is faced with increasing pressure to use new technologies to teach students the knowledge and skills they need in the 21 st century.…”
Section: Introductionmentioning
confidence: 99%